Analysis of Students’ Errors in Solving Linear Program Questions - Yeyen Vioskha; Kartini (Magister Mathematic Education Department Faculty of Teacher Training and Education Universitas Riau, 2020)
This study aims to analyze the errors of class X SMA students on linear program material. The method applied is the qualitative description method. Purposive sampling was implemented in this study, and the participants were 30 students from class X MIA SMAN 5 Tapung. The types of errors analyzed are based on Nasution's theory, which states that there are three types of errors: conceptual errors, procedural errors, and computational errors. The test questions are given in the form of 7 description questions. The results of the analysis of student answers along with the analysis of interviews, errors in calculations occur because students are not careful in calculating and entering numbers into the formula. Therefore only 8 students whose scores exceed the standard score of 70. Based on the results of the analysis of student answers, it can be concluded that, students' errors in solving linear program questions are in conceptual errors where students do not understand the implied meaning of the questions; procedural and computational errors where students are not able to carry out the procedures or steps that will be used to solve the problems, do not know the arithmetic operations that will be used to solve the problems and do not write down the final results according to the procedures or steps applied.